Comparing Fishermen Quality of Life Based on Their Expectation Toward Maslow’s Hierarchical Needs Priority - Mayta Secandina Putri (IJEEM - Indonesian Journal of Environmental Education and Management, 2017)
This study is aimed at finding out whether fishermen quality of life would differ if their expectation toward hierarchical needs such as physiological, safety, love belonging, self esteem, and self-actualization, differ also based on they put differently as priority. A survey method used by involving 73 fishermen as a sample. Two instruments were measuring quality of life and Maslow’s Needs. Instruments reliability are high and data analysed by correlational analysis, chi square, and verify by applying F and t-test. Research results show that around 80% of fishermen put physiological needs as the most priority, but not followed by safety need. It has been followed by love belonging as second priority, then safety, self-esteem, finally self-actualization. It is also found that there is no significant differences of quality of life between fishermen expectation, whether they put needs as priority or not. It could be concluded that fishermen expectation toward their needs can not be used in analysing the effect of needs on quality of life and needs are not a good predictor as well. The surprising finding is that fishermen from this area put belonging as a second hierarchy.